2014
DOI: 10.4103/1658-354x.130713
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic effectiveness of topical levobupivacaine 0.75% versus topical proparacaine 0.5% for intravitreal injections

Abstract: Background and Purpose:Today no method of topical anesthesia for intravitreal injection administration has been proven to make the patient comfortable yet. We compared the efficacy of topical levobupivacaine 0.75% and proparacaine 0.5% in patients undergoing intravitreal injections.Materials and Methods:A prospective, randomized study comparing two agents for topical anesthesia in intravitreal injections. Ninety-six consecutive patients were enrolled into two groups to receive either topical levobupivacaine 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Topical drops provided excellent anesthesia in a quick, comfortable, and safe manner for IVIG2: 0.5% topical tetracaineG2: 2.8G3: topical proparacaine + 4% lidocaine pledgetG3: 2.3G4: topical proparacaine + SC injection of 2% lidocaineG4: 3.1 p  = 0.28Yau et al [11] (Canada)To compare the anesthetic effectiveness of three topical agents used for IVIs93Group 1: 83.6G1: 0.5% tetracaine hydrochloride drops + 4% lidocaine pledget for 10Patients graded pain on a 100-mm VAS, or by saying a number from 0 to 100RNZG1: 19 (12–26)No clinical (statistical) difference in patient pain between the three topical agents tested. The addition of a 4% lidocaine pledget for 10” offered no clinical advantage in pain relief compared to 0.5% tetracaine or 4% cocaine drops aloneGroup 2: 79.5G2: 0.5% tetracaine hydrochloride dropsG2: 21 (13–29)Group 3: 82.1G3: 4% cocaine + epinephrine 1/100.000 dropsG3: 21 (16–27)Örnek et al [14] (Turkey)To compare the efficacy of topical 0.75% levobupivacaine and 0.5% proparacaine9663.97G1: 0.75% levobupivacaine dropsPatients graded pain on a 100-mm VASRNZ, TACG1: 44.77 ± 16.420.5% topical proparacaine was more effective than 0.75% topical levobupivacaine in preventing pain during IVIG2: 0.5% proparacaine dropsG2: 34.18 ± 14.83 p  = 0.003Shiroma et al [1] (Brazil)To investigate the safety and anesthetic efficacy of five concentrations of lidocaine gel26070.1G1: 2% lidocaine gelPatients graded pain on a 0 to 10 scaleRNZG1: 2.63 ± 1.68Lidocaine gel at concentrations from 2% to 12% induced similar anesthetic effect for IVIG2: 3.5% lidocaine gelG2: 2.08 ± 1.35G3: 5% lidocaine gelG3: 2.00 ± 1.65G4: 8% lidocaine gelG4: 1.93 ± 1.40<...>…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical drops provided excellent anesthesia in a quick, comfortable, and safe manner for IVIG2: 0.5% topical tetracaineG2: 2.8G3: topical proparacaine + 4% lidocaine pledgetG3: 2.3G4: topical proparacaine + SC injection of 2% lidocaineG4: 3.1 p  = 0.28Yau et al [11] (Canada)To compare the anesthetic effectiveness of three topical agents used for IVIs93Group 1: 83.6G1: 0.5% tetracaine hydrochloride drops + 4% lidocaine pledget for 10Patients graded pain on a 100-mm VAS, or by saying a number from 0 to 100RNZG1: 19 (12–26)No clinical (statistical) difference in patient pain between the three topical agents tested. The addition of a 4% lidocaine pledget for 10” offered no clinical advantage in pain relief compared to 0.5% tetracaine or 4% cocaine drops aloneGroup 2: 79.5G2: 0.5% tetracaine hydrochloride dropsG2: 21 (13–29)Group 3: 82.1G3: 4% cocaine + epinephrine 1/100.000 dropsG3: 21 (16–27)Örnek et al [14] (Turkey)To compare the efficacy of topical 0.75% levobupivacaine and 0.5% proparacaine9663.97G1: 0.75% levobupivacaine dropsPatients graded pain on a 100-mm VASRNZ, TACG1: 44.77 ± 16.420.5% topical proparacaine was more effective than 0.75% topical levobupivacaine in preventing pain during IVIG2: 0.5% proparacaine dropsG2: 34.18 ± 14.83 p  = 0.003Shiroma et al [1] (Brazil)To investigate the safety and anesthetic efficacy of five concentrations of lidocaine gel26070.1G1: 2% lidocaine gelPatients graded pain on a 0 to 10 scaleRNZG1: 2.63 ± 1.68Lidocaine gel at concentrations from 2% to 12% induced similar anesthetic effect for IVIG2: 3.5% lidocaine gelG2: 2.08 ± 1.35G3: 5% lidocaine gelG3: 2.00 ± 1.65G4: 8% lidocaine gelG4: 1.93 ± 1.40<...>…”
Section: Resultsmentioning
confidence: 99%
“…Only six studies evaluated pain at the moment of IVI [1, 2, 5, 6, 11, 14]. On the other hand, Blaha et al [16] and Kumar et al [15] considered a combined score calculated by adding the discomfort for anesthesia and the IVI.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the aforementioned factors, there have been some reports on differences in the degree of pain according to age [ 8 14 16 ], type of anaesthetic [ 4 7 11 21 ], and location of injection [ 12 22 ]. Rifkin and Schaal [ 14 ] reported that older patients perceived more pain during intravitreal injections; however, others reported that older patients were associated with lower degree of pain [ 8 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Örnek et al, reported that levobupivacaine resulted in statistically significantly higher pain scores than proparacaine (4.477 vs 3.418, respectively). 11 Of note, no other study has reported on the use of levobupivacaine for intravitreal injections and did not appear as a commonly used anesthetic in the surveys among ophthalmologists. Ultimately, no author recommended the use of any one of the anesthetics over another.…”
Section: Topical Anesthetics Anesthetic Dropsmentioning
confidence: 97%
“…Two studies, by Yau and Blaha et al, used a single drop prior to IVI whereas three, by Sanabria, Rifkin, and Örnek et al, used multiple drops over the span of minutes prior to IVI. [7][8][9][10][11] The Blaha study also administered one additional drop of anesthetic after the injection. Each of the above had the patient evaluate the pain of the injection on a 10-point or 100-point visual analog scale immediately after IVI.…”
Section: Topical Anesthetics Anesthetic Dropsmentioning
confidence: 99%